Little man inside us - Cheah, Pike See; Tan, Niu Jin; Mok, Pooi Ling; Leong, Pui Yee; Ling, King Hwa (Universiti Putra Malaysia Press, 2016)
The concept of ‘homunculus’ (“little man” in Greek) was mentioned in psychology and brain anatomy in 19th century, specifically in brain mapping to different body parts. The brain is connected by many sensory and motor neurones. Hence, our brain sees two different homunculi in us - the sensory and the motor homunculus. Contrary to how we perceive ourselves, our brain could actually ‘see’ us as Gollum in Lord of the Rings.